2017
DOI: 10.4103/1008-682x.173453
|View full text |Cite
|
Sign up to set email alerts
|

Transperineal prostate biopsies for diagnosis of prostate cancer are well tolerated: a prospective study using patient-reported outcome measures

Abstract: We aimed to determine short-term patient-reported outcomes in men having general anesthetic transperineal (TP) prostate biopsies. A prospective cohort study was performed in men having a diagnostic TP biopsy. This was done using a validated and adapted questionnaire immediately post-biopsy and at follow-up of between 7 and 14 days across three tertiary referral hospitals with a response rate of 51.6%. Immediately after biopsy 43/201 (21.4%) of men felt light-headed, syncopal, or suffered syncope. Fifty-three p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
2
13
1
1
Order By: Relevance
“…This trend is similar to that of Dobruch J et al and Wadhwa et al who recorded the most prevalent moderate LUTS among European men who had prostate biopsy [13,14]. No clear reason has been adduced for these findings except that Dobruch found that most men with localized prostate carcinoma are found in this group of LUTS [13].…”
Section: Discussionsupporting
confidence: 87%
“…This trend is similar to that of Dobruch J et al and Wadhwa et al who recorded the most prevalent moderate LUTS among European men who had prostate biopsy [13,14]. No clear reason has been adduced for these findings except that Dobruch found that most men with localized prostate carcinoma are found in this group of LUTS [13].…”
Section: Discussionsupporting
confidence: 87%
“…Our study adds to literature on PROMs following prostate biopsies through the transperineal route. [15][16][17] Our study differs in that it is the first to report PROMs on men who exclusively underwent a TTPM-biopsy following a prior TRUS-biopsy. The first prospective collection of PROMs data for transperineal biopsies was reported by Wadhwa et al 17 This study only evaluated the short-term PROMs months from the procedure.…”
Section: Discussionmentioning
confidence: 93%
“…[15][16][17] Our study differs in that it is the first to report PROMs on men who exclusively underwent a TTPM-biopsy following a prior TRUS-biopsy. The first prospective collection of PROMs data for transperineal biopsies was reported by Wadhwa et al 17 This study only evaluated the short-term PROMs months from the procedure. 18 Their study did however used the shorter form of the IIEF questionnaire and also performed a lower number of cores in comparison to our study which was 5mm mapping biopsy of each prostate.…”
Section: Discussionmentioning
confidence: 93%
“…Nevertheless, as described in the introduction, transperineal systematic biopsies cannot yet be safely omitted in favor of a TB only approach. Moreover, they are well tolerated and have only minor, temporarily side effects like hematuria, short-term catheterization, erectile deterioration, or fever with no septic complications being reported [32] . Thus, patients seem to handle them at least as good as conventional TRUS biopsy [33] .…”
Section: Discussionmentioning
confidence: 99%